Morphology vs. taxonomy in the family Pandanaceae: a case study in the Javanese species - Sri Endarti Rahayu; Tatik Chikmawati; Kuswata Kartawinata; Alex Hartana (Reinwardtia, 2012)
Since a large number of characters are now known for Freycinetia Gaudich. and Pandanus Parkinson species, it appears useful to consider their use in identifying plants from Java. Fieldwork carried out for this study has provided stronger foundation for understanding morphological variation within the species. This study was undertaken to have a better understanding on the morphology of the family in order to make a better species delimitation. Characters of habit, stem, leaves, auricles, bracts, peduncle and pedicel, inflorescence, staminate flowers (male), pistillate flowers (female), cephalia and berries were found useful in delimitation and identification of Javanese Freycinetia, while characters of habit, stem, prop root, marginal spine, leaves, bracts, inflorescentia, peduncle, staminate flowers (male), pistillate flowers (female), cephalia, drupes were found to be useful for distinguishing among species of Javanese Pandanus.